Linkage disequilibrium analyses in the Costa Rican population suggests discrete gene loci for schizophrenia at 8p23.1 and 8q13.3 - Walss Bass, Consuelo (2006)
Linkage studies using multiplex families have repeatedly implicated chromosome 8 as involved in schizophrenia etiology. The reported areas of linkage, however, span a wide chromosomal region. The present study used the founder population of the Central Valley of Costa Rica and phenotyping strategies alternative to DSM-IV classifications in attempts to further delimitate the areas on chromosome 8 that may harbor schizophrenia susceptibility genes. A linkage disequilibrium screen of chromosome 8 was performed using family trios of individuals with a history of psychosis. Four discrete regions showing evidence of association (nominal P values less than 0.05) to the phenotype of schizophrenia were identified: 8p23.1, 8p21.3, 8q13.3 and 8q24.3. The region of 8p23.1 precisely overlaps a region showing strong evidence of linkage disequilibrium for severe bipolar disorder in Costa Rica. The same chromosomal regions were identified when the broader phenotype definition of all individuals with functional psychosis was used for analyses. Stratification of the psychotic sample by history of mania suggests that the 8q13.3 locus may be preferentially associated with non-manic psychosis. These results may be helpful in targeting specific areas to be analyzed in association-based or linkage disequilibrium-based studies, for researchers who have found evidence of linkage to schizophrenia on chromosome 8 within their previous studies.